Inhibition mechanism and antibacterial activity of natural antibacterial agent citral on bamboo mould and its anti-mildew effect on bamboo - Zhang, Jingjing (R Soc Open Sci, 2021)
Bamboo, a natural material, has been widely used in the fields of decoration, architecture and furniture. However, bamboo is easy to mildew and lose its use value. In this paper, the inhibition mechanism and antibacterial activity of a natural antibacterial agent citral on bamboo mould and its anti-mildew effect on bamboo were studied. The results showed that citral could change the shape of mycelium, destroy the integrity of mycelium structure, cell wall and cell membrane structure, thereby causing leakage of nucleic acids, proteins and other substances in the cell, as well as destroy the pH balance of the inside and outside of the cell, to inhibit or kill mould. When the concentration of citral is 100 mg ml(−1), the antibacterial rates of citral against Penicillium citrinum (PC), Trichoderma viride (TV), Aspergillus niger (AN) and a hybrid fungi group comprising PC, TV and AN (Hun) were more than 100%. However, compared with the direct effect of citral on mould, the antibacterial property of bamboo treated with citral was significantly reduced, the mildew proof effect can be achieved only if the concentration of citral to treat bamboo is increased to more than twice the concentration of citral directly acting on mould.